2017
DOI: 10.1002/jat.3545
|View full text |Cite
|
Sign up to set email alerts
|

Integration of mechanistic and pharmacokinetic information to derive oral reference dose and margin‐of‐exposure values for hexavalent chromium

Abstract: The current US Environmental Protection Agency (EPA) reference dose (RfD) for oral exposure to chromium, 0.003 mg kg−1 day−1, is based on a no‐observable‐adverse‐effect‐level from a 1958 bioassay of rats exposed to ≤25 ppm hexavalent chromium [Cr(VI)] in drinking water. EPA characterizes the confidence in this RfD as “low.” A more recent cancer bioassay indicates that Cr(VI) in drinking water is carcinogenic to mice at ≥30 ppm. To assess whether the existing RfD is health protective, neoplastic and non‐neoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Most chromium in groundwater sources is Cr(VI) (Seidel & Corwin, 2013) and US Environmental Protection Agency's (EPA) own environmental monitoring data indicate median and 95th percentile Cr(VI) levels of 0.001 and 0.003 ppm, 2 respectively, resulting in daily exposures on the order of 3E-5 to 9E-5 mg/kg/day. Adjusting the dichromate benchmark dose lower confidence limit (BMDL) for intestinal tumors in mice listed in Table 1 of Chepelev et al to Cr(VI) results in MOE values above 10,000, as does our previous analyses on the oral tumors in rats (Thompson et al, 2018). Notably, Health Canada (2016) lists estimated daily exposures to Cr(VI) as 0.065 μg/kg/day, which also results in MOEs >10,000.…”
Section: To the Editormentioning
confidence: 68%
“…Most chromium in groundwater sources is Cr(VI) (Seidel & Corwin, 2013) and US Environmental Protection Agency's (EPA) own environmental monitoring data indicate median and 95th percentile Cr(VI) levels of 0.001 and 0.003 ppm, 2 respectively, resulting in daily exposures on the order of 3E-5 to 9E-5 mg/kg/day. Adjusting the dichromate benchmark dose lower confidence limit (BMDL) for intestinal tumors in mice listed in Table 1 of Chepelev et al to Cr(VI) results in MOE values above 10,000, as does our previous analyses on the oral tumors in rats (Thompson et al, 2018). Notably, Health Canada (2016) lists estimated daily exposures to Cr(VI) as 0.065 μg/kg/day, which also results in MOEs >10,000.…”
Section: To the Editormentioning
confidence: 68%
“…These examples highlight the importance of evaluating model fit to ultimately determine which model should be used to derive final BMD estimates ( Figure 3 ). Trainees are lastly pointed to example dose-response publications that have addressed environmental health questions ( Rager et al, 2017 ; Auerbach and Paules, 2018 ; Thompson et al, 2018 ; Johnson et al, 2020 ), as well as additional modeling tools and guidance documents surrounding dose-response assessments. The importance of this module is that BMD modeling represents a foundational topic in environmental health, where methods can be used to better understand which exposure concentrations/doses are required to elicit toxicity by evaluating trends in datasets.…”
Section: Resultsmentioning
confidence: 99%
“…at least 6-12 months). For Cr(VI), the human equivalent dose (HED) in mg/kg for duodenal hyperplasia was estimated from mice to be 0.02 mg/kg-day (Thompson et al 2018), which is equivalent to 0.54 ppm of Cr(VI) in drinking water daily for a lifetime, based on the 95th %-ile drinking water intake of 37 ml/kg-day (U.S. EPA 2019). This is 180-fold higher than the 95th %-ile Cr(VI) concentration in U.S. drinking water of 3 ppb.…”
Section: Biological Domain Of Applicabilitymentioning
confidence: 99%
“…A rather large number of studies targeted at informing risk assessment of Cr(VI) were conducted from $2010 to 2019, including pharmacokinetics (Kirman et al 2012(Kirman et al , 2013(Kirman et al , 2016(Kirman et al , 2017Proctor et al 2012;De Flora et al 2016), in vivo genotoxicity assays (De Flora et al 2008;O'Brien et al 2013;Thompson, Young, et al 2015;2017;Aoki et al 2019), transcriptomic analyses Thompson, Gregory, et al 2012;Rager et al 2017), and histopathological analyses Cullen et al 2016). Based on this large body of new information, both the scientists directly involved in the research as well as others reviewing the work have concluded that Cr(VI) causes SI cancer through a non-mutagenic MOA and that non-linear risk assessment approaches are most appropriate (Thompson et al 2014;Haney 2015;Health Canada 2016;TCEQ 2016;Thompson et al 2018;FSCJ 2019;WHO 2019).…”
mentioning
confidence: 99%